2016
DOI: 10.14198/jhse.2016.11.proc1.12
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of sport specific skills of football players

Abstract: The Institute of Sport Science at the University of West-Hungary, and the FH-Joanneum -together with students majoring in sport science -started a collaborative international research aimed at assessing the sport-specific skills of football players. The study closely monitored football players -from leagues at different levels -in terms of choice reaction time, short and long pass skills and agility skills with and without a ball. The most modern device available, the SmartSpeed -a photoelectric stopwatch syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Based on this study, it can be concluded that agility is an extremely complex ability, as other authors have a similar view (Bloomfield et al, 1994;Buttifant et al, 2002;Bangsbo & Mohr, 2012), and its connection to other skills and performance components is hard to define (Sheppard & Young, 2006;Koltai et al, 2016), so it is significance for soccer is quite immense (Radák, 2019). The agility tests AWB or AWOB belong to motor tests organically in the case of young soccer players (Momčilović et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Based on this study, it can be concluded that agility is an extremely complex ability, as other authors have a similar view (Bloomfield et al, 1994;Buttifant et al, 2002;Bangsbo & Mohr, 2012), and its connection to other skills and performance components is hard to define (Sheppard & Young, 2006;Koltai et al, 2016), so it is significance for soccer is quite immense (Radák, 2019). The agility tests AWB or AWOB belong to motor tests organically in the case of young soccer players (Momčilović et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Some authors associate agility with coordination skills (Katics, 2015). Agility performance may vary at different training levels, but not necessarily those in the highest level achieve the best results (Koltai et al, 2016). Overall, it can be stated that the relationship between agility and different endurance abilities or traditional coordination abilities cannot be clearly demonstrated (Sever & Zorba, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…the result of the open context test in the present study differs from research that did not find significant superiority in the performance of players of more advanced categories in open skills. Examples include the comparison of futsal players of U-7, U-9, and U-11 categories in the percentage of successful offensive technical actions based on observations of game footage [11], as well as the study by Koltai et al [21] with soccer players of different age categories (U-15, U-17, and professional) evaluated with a test similar to the open context test applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The performance determining role of the different abilities and skills has already been the basis of our researches. We were examining the connection of technical preparedness with the ball and the choice reaction [27], and also the optimal body composition and the effect of endurance to the ability of change of direction measured with standardized field tests [28]. In our opinion these are the key components that being completed with performance monitoring determine the performance of the successful football player.…”
Section: Introductionmentioning
confidence: 99%